Heroines and History : Representations of Madeleine de Verchères and Laura Secord - Coates, Colin MacMillan, 1960- (Book collections on Project MUSE., 2002)
"Heroines and History is a co-authored, comparative study of the images of Madeleine de Vercheres and Laura Secord, symbols respectively of French-Canadian and English-Canadian loyalism and nationalism. The authors explore the roles of gender, race/ethnicity, and imperialism in defining national identity and shaping the past by looking at the role of local historical societies, the formation of narratives of Loyalism and the War of 1812 in school texts, and the use of historical figures in the service of twentieth-century consumer capitalism (e.g., the Secord chocolate company) and in the development of tourism." "This is a fascinating comparison of the histories of Ontario and Quebec as seen through the handling of their best-known heroines. Most Canadians are familiar with stories of Madeleine de Vercheres defending Montreal against the Iroquois in 1692 and of Laura Secord and her cow bravely crossing the American lines to warn the British during the War of 1812. In both cases, the authors show how these heroines were used for nationalistic purposes in their respective provinces, and how their images changed down through the ages." "Heroines and History makes a significant contribution to the growing body of literature on commemoration, as well as to the literatures of gender, cultural, and Aboriginal studies. It will be of interest both to specialist academic readers and general readers of Canadian history and society."--Jacket